DESIGN OF CRYPTOCURRENCY INVESTMENT TRANSACTION MODEL AS AN EFFORT TO INCREASE STATE REVENUE THROUGH DIGITAL ASSET INSTRUMENT RATES AND TAXES IN INDONESIA - Mohd. Heikal; Rico Nur Ilham; Muammar Khaddafi; Fuadi; Muhammad Multazam; Fauzi Pakpahan (CV. Radja Publika, 2023)
This research will discuss the design of cryptocurrency transaction models as an effort to increase state income. The main factor that must be met in order to be legal in Indonesia is special regulations related to cryptocurrency. Developing special regulations related to cryptocurrency is actually an important step for the Indonesian state. For example, in developed countries such as the United States, Japan and Singapore, tax regulations related to cryptocurrency have been prepared. Especially at this time, technological developments, especially digital or virtual systems, are very rapid. So it can be predicted that various new virtual currencies that are similar or even more sophisticated and more complex than the ones that exist today will continue to emerge in the future. Determining the basis for tax levies for Cryptocurrency digital assets needs to be done based on the virtual currency units or also based on their value when converted to foreign currency such as rupiah or USD. Apart from that, it is also necessary to classify the type of tax that will be imposed on Cryptocurrency, whether it will be the object of income tax (PPh 21), profit income tax on exchange rate differences or income tax on capital gains (PPh article 4 paragraph 2) or VAT. This research actually started with attention to the many demands from Bitcoin users in Indonesia who wanted to have legal protection rights in the cryptocurrency transaction process, because in several other countries such as Singapore Bitcoin has become a legal financial investment option and is regulated and supervised by the government and the State Financial Authority. the. So the researcher intends to study in more depth how the Cryptocurrency transaction system can be supervised and controlled by the government, so that later a